1976
DOI: 10.1073/pnas.73.3.762
|View full text |Cite
|
Sign up to set email alerts
|

Receptor interactions in a signalling system: competition between ribose receptor and galactose receptor in the chemotaxis response.

Abstract: Galactose and ribose receptors are shown to compete for a common site by comparing the specificities of the purified receptors with the specificity of the whole organism response. Ribose does not bind to the purified galactose receptor but inhibits the in vivo galactose response. A mutant lacking the ribose receptor shows no inhibition of the galactose response even at very high ribose concentrations. The results can. be explained by a mechanism involving (a) a ligand-induced conformational change in the recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
33
0

Year Published

1977
1977
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 26 publications
(13 reference statements)
5
33
0
Order By: Relevance
“…The signaller, defined by experiments on galactose and ribose chemotaxis in enteric bacteria, is a protein that monitors the number of binding proteins occupied by attractant. If competing-attractantreceptor complexes occupy most of the signallers, then the signallers will be less able to detect attractantreceptor complexes so that chemotaxis toward the attractant will be impaired (see, for example, Strange & Koshland, 1976). (iii) Each can be sensed by different receptors, but the competing attractant can also bind at the attractant's receptor as an antagonist.…”
Section: Specificity Of Chemoreceptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The signaller, defined by experiments on galactose and ribose chemotaxis in enteric bacteria, is a protein that monitors the number of binding proteins occupied by attractant. If competing-attractantreceptor complexes occupy most of the signallers, then the signallers will be less able to detect attractantreceptor complexes so that chemotaxis toward the attractant will be impaired (see, for example, Strange & Koshland, 1976). (iii) Each can be sensed by different receptors, but the competing attractant can also bind at the attractant's receptor as an antagonist.…”
Section: Specificity Of Chemoreceptorsmentioning
confidence: 99%
“…(i) Both can be sensed by the same receptor (binding protein). (ii) Each can be sensed by different receptors (binding proteins), but both receptors can have a 'signaller' in common (Ordal & Adler, 1974;Strange & Koshland, 1976). The signaller, defined by experiments on galactose and ribose chemotaxis in enteric bacteria, is a protein that monitors the number of binding proteins occupied by attractant.…”
Section: Specificity Of Chemoreceptorsmentioning
confidence: 99%
“…Trg generates sensory information about external concentrations of ribose and galactose by interacting with ligand-occupied ribose-and galactosebinding proteins, respectively (16,24). Competition experiments have shown that the presence of one sugar inhibits tactic response to the other sugar (2,10,39). A simple model for the competition is that the transducer has a single, common interaction site for both ligand-occupied binding proteins (39).…”
mentioning
confidence: 99%
“…2 shows a schematic version of the receptor based on our current knowledge. The "floating receptor" mechanism appears to be well established for the interaction of the ribosebinding protein and the galactose-binding protein with the trg gene product (29,30). Competition studies show that the galactose-galactose-binding-protein complex and the riboseribose-binding-protein complex compete for a limited number of trg sites in the membrane (29).…”
mentioning
confidence: 99%
“…The "floating receptor" mechanism appears to be well established for the interaction of the ribosebinding protein and the galactose-binding protein with the trg gene product (29,30). Competition studies show that the galactose-galactose-binding-protein complex and the riboseribose-binding-protein complex compete for a limited number of trg sites in the membrane (29). Mutations affecting the galactose-binding protein eliminate galactose-taxis (9); mutations affecting the ribose-binding protein eliminate ribose-taxis (7), and mutations affecting the trg protein eliminate both (31).…”
mentioning
confidence: 99%